Purification Of A Hemostasis Activating Factor (HAF) From Human And Porcine Subcutaneous Tissue - Bender, N; Kirchmaier, C M; Breddin, K (Thrombosis and Haemostasis, 1981)
Platelet shape change up to 90% was induced in freshly drawn citrated blood after incubation with small amounts of porcine or human subcutaneous tissue extract for 2-3 seconds. The normal value of platelets with pseudopodes in freshly drawn blood is about 20 to 25%. Subcutaneous tissue was suspended in 30% propanol in a ratio of 1:4 (v/v) after passing a meat chopper. It sedimented after centrifugation (25 min at 100G) in four zones: an upper and lower lipid layer, a liquid intermediate zone and a pellet containing tissue particles and cell fragments. The highest platelet stimulating activity (= Hemostasis activating Factor) was found in the liquid intermediate zone, which contained total lipid concentrations of 140 mg% to 160 mg%, protein concentrations of 0.15 mg/ml to 0.3 mg/ml and an osmolarity 900 to 1000 mOsm. This intermediate zone was separated into two peaks by gelfiltration on Sephadex G 50. Fractions of the second peak contained the highest platelet stimulating activity. After ultrafiltration of the intermediate zone through Amicon CF 25 cones the activity was found in the ultrafiltrate. The ultrafiltrate has been lyophilised without losing its activity. 2.5μg/ml lyophilised HAF induced shape change in more than 90% of human platelets in freshly drawn whole or citrated blood after incubation for 1 min at 37°C. The lyophilised material contained 11 peptides which were identified by gelchromatography and peptide fingerprinting. However, none of them showed any platelet stimulating activity. The peptide patterns of human HAF and HAF from porcine subcutaneous tissue were identical. As revealed by thinlayer chromatography in different solvents most of the lipid compounds of lyophilised HAS were phospholipids. Besides others cephalin, cardiolipin and phosphatidylcholin have been identified. It seems likely that a mixture of peptides with phospholipids is essential for the platelet stimulating activity.